2018
DOI: 10.1002/ejlt.201700288
|View full text |Cite
|
Sign up to set email alerts
|

Corn Lecithin for Injection from Deoiled Corn Germ: Extraction, Composition, and Emulsifying Properties

Abstract: Although the lipid fraction of corn germ is rich in lecithin, this material is usually discarded with the residual pulp during industrial corn oil extraction processes. In this study, corn germ, after deoiling by supercritical carbon dioxide (SCCO2), is used as a raw material to prepare corn lecithin for injection. The physicochemical properties, phospholipid composition, fatty acid composition, and emulsifying properties of the corn lecithin for injection is analyzed. The phospholipid and phosphatidylcholine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Lecithin is a high-quality additive component, which exhibits advantageous interfacial properties and has aroused increasing interest as a natural emulsifier in the food, pharmaceutical and cosmetics industries (24). It comprises a concentrated mixture of phospholipids (PL) such as phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidic acid (PA) and phosphatidylserine (PS) (24). Lecithin is usually extracted through multi-stage solvent extraction (24).…”
Section: Phospholipids As a Functional Ingredientmentioning
confidence: 99%
See 2 more Smart Citations
“…Lecithin is a high-quality additive component, which exhibits advantageous interfacial properties and has aroused increasing interest as a natural emulsifier in the food, pharmaceutical and cosmetics industries (24). It comprises a concentrated mixture of phospholipids (PL) such as phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI), phosphatidic acid (PA) and phosphatidylserine (PS) (24). Lecithin is usually extracted through multi-stage solvent extraction (24).…”
Section: Phospholipids As a Functional Ingredientmentioning
confidence: 99%
“…The residual maize germ meal left after the maize germ oil extraction is usually discarded but is rich in lecithin. Lecithin is a high-quality additive component, which exhibits advantageous interfacial properties and has aroused increasing interest as a natural emulsifier in the food, pharmaceutical and cosmetic industries ( 24 ). It comprises a concentrated mixture of phospholipids such as phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, phosphatidic acid and phosphatidylserine ( 24 ).…”
Section: Phytochemical Components Of Maize Wet Milling By-productsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, lowtemperature storage can inhibit the development of the LIF system in an unstable direction. The change trend of TSI value with different storage conditions may be International Journal of Food Science and Technology 2024 related to the clarification, coalescence, flocculation and sedimentation that occurred in the bottom, middle and top regions of the sample (Liu et al, 2018), and this study was similar to previous study that the changes of TSI values were indeed consistent with the changes of the particle size of the LIF system (Chen & Sagis, 2019). The changes of TSI and particle size during storage indicated that the stability of LIF at low-temperature storage was better than that at room temperature and high-temperature storage.…”
Section: Analysis Of Tsimentioning
confidence: 99%
“…Corn germ is rich in amphiphilic molecules called phospholipids. Corn germ is high in lecithin, which is a high-quality additive component that exhibits advantageous interfacial properties and has attracted increasing interest as a natural emulsifier in the food, pharmaceutical and cosmetic industries [ 129 ]. It comprises a concentrated mixture of phospholipids such as phosphatidylcholine, phosphatidylethanolamine, phosphatidylinositol, phosphatidic acid and phosphatidylserine [ 61 ].…”
Section: Phospholipids In Cornmentioning
confidence: 99%